EFSA's activities on emerging risks in 2017. Issue 1 (14th January 2019) - ,; Afonso, Ana; Garcia Matas, Raquel; Maggiore, Angelo; Merten, Caroline; Rortais, Agnes; Huang, Taya; Robinson, Tobin
Abstract : The main objectives of EFSA's activities on emerging risks are: (i) to carry out activities to identify emerging risks in the areas within the remit of EFSA; and (ii) to develop and improve emerging risk identification methodologies and approaches. The current technical report summarises the activities of all groups involved in the emerging risk identification procedure, the issues identified in the course of 2017, a description of methodologies being developed and collaborative activities.EFSA networks of knowledge include the Emerging Risks Exchange Network, the stakeholder discussion group on emerging risks, EFSA's scientific units, scientific panels and the Scientific Committee and its working groups. Summaries of emerging risk identification procedures in use by different stakeholders are presented.A project on the applicability of global food chain analysis for identification of vulnerabilities and drivers of change (AQUARIUS) and two grant agreements with Member States for the development of methodologies and collaboration tools for emerging risk identification (DEMETER) and data collection on ciguatera food poisoning in Europe (EuroCigua) are ongoing. A new project on the application of the procedure for screening chemicals (REACH 2) was initiated.A total of 17 potential emerging issues were discussed in 2017. The issues were assessed against a set of pre‐defined criteria: a) new hazard, b) new or increased exposure, c) new susceptible group, and d) new driver. Five issues were not considered to be emerging issues according to EFSA's definition.Follow‐up of developments in knowledge or measures taken concerning issues previously identified is extremely difficult and performance of the emerging risk identification procedure should not be based on numbers of issues identified but rather on the process itself. Better collaboration with the scientific community both within EFSA (EFSA units, EFSA networks, panels and working groups) and EU institutions and international organisations is a priority for EFSA but in order to make the procedure more effective, data management systems and digital collaboration platforms are necessary to manage the large amount of data and information available.